ANALISIS MATERI NAHWU DALAM KITAB AUDLOHUL MANAHIJ FI MU’JAM QOWA’IDUL LUGHOH AL ‘AROBIYAH - Suharsono Suharsono; M. Akzomi Zakawali (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
This article is aim to analyze the appropriated of Nahwu Book to educated someone who want to learn arabic language easily. This book created by Agus Shohib Khoironi, Lc in 2001 by using Mustaqilli method for the teaching arabic language. In analizing this book, this research is a library research then analyzing by nahwu material analysis, in the other side, this research also analyzing with conducting four principles of William F. Mackey’s theory which includes: repetition, presentation, gradation, and selection. From the results of the analysis of the nahwu material in the book Audhohul Manahij Fi Mu'jam Qowaidul Lughoh Al-Arabiyah, it was found that the preparation of this book was in accordance with Mackey's theory of gradation, selection, presentation and repetition. The nahwu material is arranged in a coherent way from a discussion of the basic nahwu qoidah to more depth, starting with the kalam chapter to the Jama 'Taksir chapter in the first part of this book, which consists of 14 discussion chapters.